The Hamilton-Jacobi approach to teleparallelism - Pimentel, B. M. [UNESP]; Pompeia, P. J. [UNESP]; Rocha-Neto, J. F.D.A. (My University, 2005)
We intend to analyse the constraint structure of Teleparallelism employing the Hamilton-Jacobi formalism for singular systems. This study is conducted without using an ADM 3+1 decomposition and without fixing time gauge condition. It can be verified that the field equations constitute an integrable system. © Società Italiana di Fisica.